Pemodelan Indeks Kerukunan Umat Beragama di Indonesia Menggunakan Regresi Nonparametrik Deret Fourier Berdasarkan Fungsi Basis Sinus dan Basis Cosinus - Yossy Candra; Andrea Tri Dani; Wagimin Wagimin (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2026)
This study aims to analyze the factors suspected of influencing the Interfaith Harmony Index (IKUB) across all provinces in Indonesia and determine the best prediction model. The predictor variables suspected of influencing are the number of religious organizations, religious instructors, educational institutions, and houses of worship. The analysis was conducted using nonparametric Fourier series regression with a comparison of cosine and sine basis functions, and evaluation through MSE, RMSE, MAPE, GCV, UBR, and . The results show that the 4-oscillating cosine basis function model is the most accurate, with MSE (2.27), RMSE (1.51), MAPE (1.47), GCV (6.56), UBR (1.29×10-10)and  (86.28%), compared to the sine basic function model. This model is able to flexibly represent complex nonlinear relationship patterns and variations in IKUB between provinces. These findings demonstrate a relationship between the research variables and variations in IKUB values, thus providing a basis for understanding harmony patterns and supporting data analysis for policy considerations. While the research findings are predictive, they place greater emphasis on uncovering the relationships between variables that influence interfaith harmony.